Investigating the Association between Coping Styles and Social Identity in Adolescents of Marginal and Non-Marginal Areas - Hadis Mosafer; Behnam Khaledi-Paveh; Nader Salari; Mahmoud Rahmati (Iranian Journal of Psychiatry)
Objective: This study aimed to investigate the relationship between coping styles and social identity among adolescents residing in marginal and non-marginal areas.